Fiscal decentralisation and economic growth in Malaysia: a market preserving federalism perspective - Abd. Ghani, Judhiana; Grewal, Bhajan; Ahmed, Abdullahi D.; Mohamed Nor, Norashidah (2019)
By using fiscal datasets from 1990 to 2010 in Malaysia, a panel Dynamic-OLS (DOLS) is employed to investigate the extent to which fiscal decentralisation can support state level economic growth as proposed in the Market preserving federalism (MPF) theory. Despite having a more centralised federalism system, the result strongly shows that a fiscal decentralisation variable, (i.e. a composite ratio of decentralisation) has significant coefficient and positive relationship with state economic growth. This implies that a certain degree of fiscal decentralisation in Malaysia is able to contribute to states’ economic performance by adopting fiscal decentralisation simultaneously on both dimensions of revenue and expenditure. This validates the view that decentralisation is a multi dimentional measure. The study shows that Malaysia also would be able to benefit from a system of federalism which empowers state governments to make policies for their jurisdictions and to compete with one another for better services and higher investment. Hence, competition is the mechanism that creates incentives that result from satisfying the MPF conditions and subsequently leading to the achievement of higher state economic performance.